Respek dan Setara: Meninjau Ulang Faktor dan Solusi Masalah LGBTQ Berbasis Nilai Teologis - Yenti Krisdayanti Gulo; Tony Salurante (Sekolah Tinggi Teologi Jaffray Jakarta, 2023)
To Examining LGBTQ issues in Indonesia still requires serious time and attention. The church must be at the forefront of providing solutions for the congregation and the country. Before the situation got even worse. This article offers an equal and respectful approach to facing the problems of LGBTQ people. This is the first step that the church must think about so as to encourage the creation of new formulations that are more contextual but biblical. By using several narrations in the book of John, this research produces ways to deal with the problem of sexual deviation, especially from LGBTQ people. The church is encouraged to follow the pattern of the incarnation of Jesus by seeking, having dialogue and being open to all sinners. No longer closing himself and only highlighting his sinfulness. Especially for teenagers who are vulnerable to conditions in modern times and in the future.